Anti-inflammatory and Anti-oxidative Effects of Phytohustil® and Root Extract of Althaea officinalis L. on Macrophages in vitro - Bonaterra, Gabriel A.; Bronischewski, Kevin; Hunold, Pascal; Schwarzbach, Hans; Heinrich, Ennio-U.; Fink, Careen; Aziz-Kalbhenn, Heba; Müller, Jürgen; Kinscherf, Ralf (Frontiers in Pharmacology, 2020)
Introduction The medicinal plant marshmallow Althaea officinalis L. (A. officinalis), is used for the treatment of cough since centuries. Application of medicinal extracts of marshmallow roots shows immediate effects like a protective film on the inflamed mucosa. Because the soothing layer reduce irritation of the mucous system, a faster regeneration is supported by defense mechanisms required to protect the respiratory tract from environmental injury. Macrophages (MΦ), which belong to a group of multipurpose defensive cells, provide the first line of defense against mucosal invasive pathogens. The present study was performed to investigate, whether the herbal medicinal product has anti-inflammatory or anti-oxidative effects on pro-inflammatorily activated MΦ or after oxidative stress induction. Special attention should be payed to elucidate the effects of A. officinalis on the mechanism of intracellular defense as well as on migratory capacity of the MΦ. Results Treatment of PMA-differentiated human THP-1 MΦ with Phytohustil® increased their viability without affecting the cell number. Phytohustil® or root extracts of A. officinalis (REAo) – an active component of Phytohustil® – were able to protect human MΦ against H2O2-induced cytotoxicity and H2O2-induced ROS production. Phytohustil®, REAo or diclofenac used as anti-inflammatory reference substance, inhibited the LPS-induced release of tumor necrosis factor-alpha (TNF-α) as well as of IL6 in MΦ. Treatment with Phytohustil®, its excipients or REAo did not impair the mitochondrial membrane potential (MMP). Finally, Phytohustil® and REAo activated the migratory capacity of MΦ. Conclusion The present in vitro investigations indicate protective, i.e., anti-oxidative and anti-inflammatory effects of REAo and Phytohustil®, additionally improving the migratory capacity of MΦ. These antiinflammatory effects were similar or even better than diclofenac. Thus, our data support and may explain the positive effect of Phytohustil® observed in patients during the therapy of inflamed buccal mucosal membranes or treatment of cough.